دور الحوافز في تحقيق الولاء التنظيمي للعاملين بالمصارف السودانية دراسة حالة:المصارف العاملة بولاية الجزيرة،(2022م) - الامين, عثمان محمود; صالح, محمد الدرديري (Gezira Journal of Economic and Social Sciences, 2022)
إن الحوافز لها دورا كبيرا في تحقيق الولاء التنظيمي  للعاملين بالمؤسسات . هدفت هذه الدراسة للتعرف على دور الحوافز المادية والمعنوية في تحقيق الولاء التنظيمي للعاملين بالبنوك التجارية بولاية الجزيرة .تم إتباع المنهج الوصفي التحليلي .توصلت الدراسة إلى هنالك علاقة ذات دلالة إحصائية بين الحوافز المادية والمعنوية وتحقيق الولاء التنظيمي للعاملين بالبنوك السودانية،  ايضا تهتم الإدارة بمنح العاملين العديد من المكافئات المادية مثل مكافأة الأداء السنوي،كما أنهم يعتبرونها كافية نوعا ما لإشباع حاجاتهم . وأيضا نجد أن غالبية العاملين بالبنوك يشعرون بالرضا فيما يتعلق بنظام التأمين الصحي والمعاشى ونظام القروض والسلفيات التي تقدم لهم .تمثلت أهم التوصيات في المحافظة على نظام الحوافز المعمول به بالمصارف السودانية والاهتمام بأساليب التحفيز الحديثة التي تساعد في رفع الولاء التنظيمي .                     abstract Incentives have a major role in achieving organizational loyalty for employees in institutions. This study aimed to identify the role of material and moral incentives in achieving organizational loyalty for workers in commercial banks in the state of Gezira. The descriptive and analytical approach was followed. The study found that there is a statistically significant relationship between material and moral incentives and achieving organizational loyalty for workers in Sudanese banks. Likewise, the administration cares about granting workers some material rewards, such as the annual performance bonus, which is considered somewhat sufficient by the employees. Also, we find that the majority of bank employees are satisfied with the health and pension system and the loans and advances system used in the organization. The most important recommendations  raised by the study are to maintain the incentive system in force in the Sudanese banks; and to pay attention to modern methods of motivation that help raise organizational loyalty.